Analysis of the Impact of Applying UX Guidelines to Reduce Noise and Focus Attention - Pascual Espada, Jordán; Alonso-Virgós, Lucía; González-Crespo, Rubén (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2023)
This research work is the continuation of previous, in which a set of usability guidelines where proposed. These guidelines were obtained from various authors and recommendations. The common part of those guides was that all of them were useful to reduce the noise and focus the attention of users in web interfaces. Some of these recommendations were evaluated in very confined environments, this research tries to evaluate the possible advantage of applying every one of these recommendations, quantifying in an experiment with real users what could be the potential time gain applying every of the recommendations. We have designed a set of web applications in which the user has to complete a simple task, some of the applications fill the usability guidelines and others not. With obtained data in the experiment, the web developers could choose in a more precise way which recommendations could be implemented in their interfaces to get a more efficient user interaction.
Keywords: data entry; usability guidelines; usability recommendations; user’s behavior; web usability; Scopus(2); WOS(2)